Mercury methylation versus demethylation: main processes involved - Susana, Segade (2011)
It is well known that mercury presents high toxicity, causing a great damage to the environment and living organisms; however, its properties depend on the mercury species present. Organomercury compounds, where methylmercury is included, cause more concern. Since 60-70’s, several methylation mechanisms are known. Generally, methylmercury can be formed naturally in the aquatic environment by two general pathways: chemical methylation (abiotic) and microbial (biotic) processes. At the same time, methylmercury can be also decomposed abiotically or by the action of several demethylating microbes, or demethylators, ranging from anaerobes to aerobes. Regarding the biotic methylmercury demethylation, two distinct vias - oxidative and reductive - might be used by those microorganisms, differing in the final products obtained. In relation to the reductive processes, two pathways might occur. The first one involves the mercury resistance operon (mer) whereas the second one involves sulphide ions; however, the former is considered to be the most common pathway. Regarding the mer operon, some bacteria only carry on a narrow-spectrum operon (merA), being only able to reduce inorganic mercury (Hg(II)) to elemental mercury (Hg0). On the other hand, others beyond this operon also carry on a broad-spectrum operon (merB). These microorganisms are able to decompose methylmercury to Hg0. Taking into account all of these processes, in the present work the most referred methylation and demethylation mechanisms found in aquatic environments are discussed, as well as the environmental factors that influence them. Factors related with the inorganic mercury/methylmercury availability and those that affect directly the activity of methylators and demethylators are also referred. Generally, the relationships encountered are complex and sometimes significant shifts on the microbial communities may be observed. These changes can alter the processes involving the mercury species, as well as the final products obtained. In conclusion, the abiotic factors and the type of microorganisms that are present in the environment, including their genetic patrimony, influence significantly the presence and the type of the mercury species. Furthermore, there are environmental factors, such as redox conditions, sulphides and organic matter that also affect the mercury dynamic and the equilibrium existents.